INFLUENCE OF LOCAL RONKOLEIKIN TREATMENT UPON CLINICAL COURSE OF PURULENT WOUNDS AND FUNCTIONAL ACTIVITY OF WOUND PHAGOCYTES IN PATIENTS WITH ODONTOGENIC PHLEGMONAE - I. I. Dolgushin; L. S. Latyushina (Медицинская иммунология, 2014)
Abstract. The aim of the work was to evaluate clinical features of purulent wounds trend and functional activity of local wound phagocytes in the patients with odontogenic phlegmones in the course of local treatment with Ronkoleukin. A randomized clinical study was performed which included sixty-five patients with odontogenic phlegmones. Their age ranged from 18 to 74 years old. The group was divided in two parts, i.e., patients of a comparison group (n = 33) receiving a conventional combined drug therapy, and the persons from study group (n = 32) who were subject to local immunotherapy with Ronkoleukin, applied along with conventional therapy. It was established that the local therapy with Ronkoleikin exerts distinct positive effects, i.e., increase in wound-located lymphocytes and macrophages, acceleration of phasic dynamics of inflammatory events, augmentation of an lysosomal luminescence index (2.3-fold), enhancement of phagocytosis intensity in wound neutrophiles and macrophages (1.9-2-fold), strengthening the reserve abilities of wound neutrophils (1.3-fold). These effects create favorable conditions for elimination of pathogen and optimal healing of purulent wounds in the patients with odontogenic phlegmones.